Push It to the Limit: Identification of Novel Amino Acid Changes on the Acetolactate Synthase Enzyme of Rice That Putatively Confer High Level of Tolerance to Different Imidazolinones - Buffon, Giseli; Lamb, Thainá Inês; Lopes, Mara Cristina Barbosa; Sperotto, Raul Antonio; Timmers, Luís Fernando Saraiva Macedo (Frontiers in Bioengineering and Biotechnology, 2020)
Advancements in genetically modified herbicide tolerance technology opened a new way to manage weed populations in crop fields. Since then, many important genetically modified crops that are tolerant to various herbicides have been developed and commercialized. Herbicides primarily act by disrupting key enzymes involved in essential metabolic or physiological processes associated with growth and development of plants. Most of the herbicide tolerant plants have been developed by introducing point mutations (non-GM approach) in the target site of herbicide action, due to the advantage of easier registration/release for commercial cultivation as well as wider public acceptance. Of the various herbicides, Imidazolinones are probably the most widely targeted ones for developing herbicide tolerant crops through non-GM approach. In rice, different mutant lines presenting amino acids changes in acetolactate synthase (ALS) have the ability to tolerate different Imidazolinones, including point mutations of Glycine to Glutamate in position 628, Serine to Asparagine in position 627, and a double mutation Tryptophan to Leucine in position 548/Serine to Isoleucine in position 627. The use of specific herbicides in combination of these mutant lines provides a reliable approach to eliminate weeds in the fields. However, the continuous overuse of a single herbicide multiple times in a growing season increases the potential risk of evolution of resistant weeds, which has become a major concern in agriculture worldwide. For this reason, the development of novel mutations in ALS (Os02g30630) to generate rice plants more tolerant to Imidazolinones than the available mutant rice lines is still a hot topic in plant-herbicide interaction field. Keeping that in mind, we carried out molecular docking experiments of Imidazolinone herbicides imazapic, imazapyr, imazaquin, and imazethapyr to evaluate the interaction of these molecules in the binding cavity of ALS from rice, being able to identify the most important amino acids responsible for the stability of these four herbicides. After introducing point mutations in these specific positions (one at a time) using Alanine scanning mutagenesis method and recalculating the effect in the affinity of herbicide-ALS interaction, we were able to propose novel amino acid residues (mainly Lysine in position 230 and Arginine in position 351) on the structure of ALS presenting a highest impact in the binding of Imidazolinones to ALS when compared to the already known amino acid mutations. This rational approach allows the researcher/farmer to choose the number of point mutations to be inserted in a rice cultivar, which will be dependent on the type of Imidazolinone used. To obtain a rice cultivar capable to tolerate the four Imidazolinone tested at the same time, we suggest six amino acid mutations at positions Val170, Phe180, Lys230, Arg351, Trp548, and Ser627 in the OsALS1.